A Critical Look to the Social Investment Approach from a Gender Perspective. (26th May 2015) - Saraceno, Chiara
Abstract : The social investment approach explicitly and implicitly addresses gender issues in its proposals for reforming welfare states. It promotes women's labour force participation and suggests a re-drawing of family-state boundaries in the responsibility towards children as human capital. While appreciating the support for work-family policies and for a public responsibility in investing on children from an early age, I argue that the ideal adult worker model that underlies this approach hides, and to some degree even takes for granted, gender inequalities in both the household and the labour market. The social investment approach also undervalues the subjective and relational meaning of caring within households, while attributing to families a mainly functional role regarding societies and labour markets. In so doing, the approach causes new tensions for men and women and possibly new inequalities among women, as well as among men.